2015
DOI: 10.1007/s10964-014-0248-y
|View full text |Cite
|
Sign up to set email alerts
|

Advancing a Biopsychosocial and Contextual Model of Sleep in Adolescence: A Review and Introduction to the Special Issue

Abstract: Sleep problems in adolescence have been identified as an international public health issue. Over the past few decades, notable advances have been made in our understanding of the patterns and consequences of sleep in adolescence. Despite these important gains, there is much about the role of sleep in adolescence that remains to be understood. This Special Issue brings together studies that examine sleep as it specifically pertains to adolescent development and adjustment. In this introductory article, we argue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
134
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(145 citation statements)
references
References 297 publications
(373 reference statements)
10
134
0
1
Order By: Relevance
“…Becker et al and Shanahan et al have also reported an association between psychological morbidity and insufficient sleep (32,33). Other studies have also found an association between short sleep duration and internalizing as well as externalizing behavioral problems (34,35).…”
Section: Discussionmentioning
confidence: 93%
“…Becker et al and Shanahan et al have also reported an association between psychological morbidity and insufficient sleep (32,33). Other studies have also found an association between short sleep duration and internalizing as well as externalizing behavioral problems (34,35).…”
Section: Discussionmentioning
confidence: 93%
“…Reviews of the literature clearly document that sleep problems negatively impact academic functioning (Becker, Langberg, & Byars, 2015;Shochat, Cohen-Zion, & Tzischinsky, 2014). The impact of sleep problems and poorer academic functioning has been documented using both naturalistic and experimental studies (Astill, Van der Heijden, Van IJzendoorn, & Van Someren, 2012), though such studies have not been conducted in teens with ADHD specifically.…”
Section: Sleep Problems Adversely Impact Adolescent Functioning Academentioning
confidence: 99%
“…This is surprising since the combination of sleep and adolescence has been described as "the perfect storm" (Carskadon, 2011). A developmental psychopathology framework is needed to advance our understanding of the complex interplay among ADHD, sleep, and adolescence (Becker, Langberg, & Byars, 2015). Risk factors for sleep problems and the consequences of comorbid sleep problems and ADHD likely differ markedly between early childhood and adolescence, given decreases in parental involvement and influence and increases in demands associated with academic and extracurricular responsibilities.…”
mentioning
confidence: 99%
“…Indeed, recent reviews have concluded that sleep problems, particularly wakefulness in bed (e.g., prolonged sleep onset latency [SOL] and poor sleep efficiency [SE]), precede the development of anxiety and depression in adolescence more than the reverse (Lovato & Gradisar, 2014;McMakin & Alfano, 2015). However, in comparison to internalizing symptoms, relatively few studies have examined the role of sleep disturbance in adolescent behavior problems (Becker, Langberg, & Byars, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, further high quality longitudinal and treatment outcome studies are needed that examine the prospective and causal associations between poor sleep and behavior problems in adolescents (Becker et al, 2015;Dewald, Meijer, Oort, Kerkhof, & Bögels, 2010;Shochat et al, 2014).…”
Section: Introductionmentioning
confidence: 99%